STRATEGY FOR DEVELOPING DUYU BANGBIT VINE GARDEN AGROTOURISM IN DUYU VILLAGE, TATANGA DISTRICT, PALU CITY - Azwarni, Ummi; Mappatoba, Marhawati; Christoporus, Christoporus (AGROLAND The Agricultural Sciences Journal (e-Journal), 2025)
Central Sulawesi, especially Palu City, is one of the areas with potential for grape development. One of the grape growing areas that is currently being used as an agrotourism destination is in Duyu Village, Tatanga District, Palu City, called Kebun Anggur Duyu Bangkit. Kebun Anggur Duyu Bangkit is one of the agrotourism areas in Palu City, but the availability of grapes is still limited, and the area of ​​land is an obstacle in the development of agrotourism, so it does not support the provision of agrotourism, resulting in agrotourism management not being optimal. This study aims to determine the potential and formulate a strategy for developing Kebun Anggur Duyu Bangkit Agrotourism. The analysis used is SWOT analysis. The results of the IFAS and EFAS matrix analysis are the strength factor value (1.87), weakness factor (2.60), opportunity factor (2.41) and threat factor (1.52) so that the position of the development strategy using the SWOT diagram is in quadrant III, namely supporting the Turn Around (WO) strategy to minimize weaknesses to take advantage of existing opportunities, so that the strategy formulation is obtained including; (1) increasing production, improving visitor facilities by cooperating with related banks and SKPKD so that tourist locations have legality; (2) creating SOPs for visitors through social media so that visitors know all procedures while on vacation; (3) increasing capital so that the location of the tourist location has an agrotourism nuance for the comfort of visitors who like a lifestyle back to nature so that the opportunity for marketing grapes is high and creates jobs for the surrounding community.